Citizenship, identity and the politics of multiculturalism the rise of Muslim consciousness - Meer, Nasar 1980- (Palgrave politics of identity and citizenship series, 2010)
"This book proposes a fresh perspective on the emergence of public Muslim identities, traversing issues of Muslim-state engagement across government initiatives and church-state relations, across equalities agendas and the education system, the courts and the media"--Provided by publisher